THE VALUE OF GENDER INCLUSIVENESS IN THE NOVEL PELABUHAN TAK BERTEPI AND ITS URGENCY FOR CHILDREN'S PSYCHIC DEVELOPMENT (SARA MILLS CRITICAL DISCOURSE ANALYSIS STUDY) - Fathurahman, M; Kalsum, Umi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study raises a theme that actually has a strong relevance to the psychological development of children. It is gender inclusiveness where the purpose of this material is to provide a basic understanding of the attitudes that children should have in relation to the relationship between men and women. The approach in this study uses discourse analysis which is divided into 3. (1) macro, which studies the global meaning of a text that can be observed. (2) superstructure, which is discourse related to the framework of a text. (3) microstructure, which is the essence of discourse seen from the micro part of a sentence. Furthermore, in general, what can be concluded from this research is the mission that the main subject wants to convey in the storytelling of the novel. First, the resistance to the patriarchal system. Second, the exploration of women's attitudes in carrying out their responsibilities both in the domestic and public sectors, which actually do not need to be positioned as second or third. In addition, this material is also in line with the theory built by Vygotsky, namely the concept of socioculture and scaffolding.